Parenting motives: Validation of the Italian version of the parental care and tenderness scale - Castelli, Luigi; Garau, Tania; Carraro, Luciana (Frontiers in Psychology, 2023)
Relevant individual differences can be observed in relation to parenting motives. The Parental Care and Tenderness (PCAT; Buckels et al., 2015) scale is an important tool aimed at assessing them. We here investigated the psychometric properties of an Italian version of the scale (N = 946). The scale had a very high reliability and its internal structure closely reproduced the one obtained in different cultural contexts. Two major subscales, namely nurturance and protection, could be identified. In addition, we explored the validity of the scale in relation to a novel domain. Individual differences in parenting motivations, and more specifically those related to nurturance, emerged to be associated with a spontaneous behavioral tendency to approach children. Scores in the PCAT, and more specifically scores in the protection subscale, were also associated with a more conservative political orientation. The present work contributes to the growing literature about the key role of parenting motives in affecting social behaviors.